2002
DOI: 10.1046/j.1365-2389.2002.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

The soil skeleton, a forgotten pool of carbon and nitrogen in soil

Abstract: Summary To evaluate the contribution of rock fragments to the soil’s total carbon content, the soil of 26 sites, ranging from the Canadian Arctic to the Jordan desert, was analysed for the content of organic C and total N in both fine earth and skeleton fractions. The soils, uncultivated and cultivated, are derived from 11 parent materials: sandstone, mica‐schist, granite, gneiss, basaltic pyroclastites, trachyte, dolomite, beach deposits, clay schist, marl and serpentinite. For each soil horizon the contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 19 publications
(25 reference statements)
4
49
0
Order By: Relevance
“…Summarizing, the OC content is very low in the quarry soils (Table 2), and it is directly related to the presence of vegetation (Table 1). This is because the serpentinite barely contributes to the C and N pools of the soils (Corti et al, 2002). In fact, the N content in the soils is very low: it was not detected in S1, S3 and S4 and in S2 it is moderately low.…”
Section: Characterization Of the Soilsmentioning
confidence: 93%
“…Summarizing, the OC content is very low in the quarry soils (Table 2), and it is directly related to the presence of vegetation (Table 1). This is because the serpentinite barely contributes to the C and N pools of the soils (Corti et al, 2002). In fact, the N content in the soils is very low: it was not detected in S1, S3 and S4 and in S2 it is moderately low.…”
Section: Characterization Of the Soilsmentioning
confidence: 93%
“…One important feature is the relative proportion of coarse fragments (>2mm in size) per unit volume, that may influence the carbon stock in the whole profile (Corti et al 2002). Another important feature to consider in evaluating OC stock is the variability of soil thickness, which in turn is a function of topography, vegetation cover and soil development.…”
Section: Soil Carbon Stock Calculationmentioning
confidence: 99%
“…However, while the equations given in IPCC resemble M3, IPCC provides a footnote that is most likely often overlooked, which states that BD estimates should be corrected for the proportion of "coarse fragments" (IPCC, 2003). Even if the rock fragment fraction might store a certain amount of organic carbon (Corti et al, 2002), which might lead to slight underestimation of SOC stocks in M4, we suggest use of this method in future studies.…”
Section: Evaluation Of the Four Different Calculation Methodsmentioning
confidence: 99%
“…The content of elements such as carbon and nitrogen in soils is usually determined in an aliquot sample of the fine soil, which is defined as the part of the soil that passes through a 2 mm sieve (Corti et al, 1998). Coarse mineral fragments > 2 mm, in the following referred to as rock fragments (Poesen and Lavee, 1994), are considered free of SOC (Perruchoud et al, 2000), although this may not be completely true as shown by Corti et al (2002). Furthermore, living root fragments > 2mm are not considered part of SOC, but usually as part of plant biomass.…”
Section: Introductionmentioning
confidence: 99%